2022
DOI: 10.1108/sgpe-02-2022-0014
|View full text |Cite
|
Sign up to set email alerts
|

Agency and career indecision among biological science graduate students

Abstract: Purpose The purpose of this study is to examine how student agency influences career decision-making for doctoral students in biological sciences. The authors address the following questions: How do biological science graduate students navigate career indecision? And how does agency relate to their experiences with career indecision? Design/methodology/approach The authors analyzed interview data collected from 84 PhD biology graduate students. Researchers used a grounded theory approach. After open codes we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 37 publications
0
9
0
Order By: Relevance
“…This powerful interest in an academic career is related to the research training that they receive during doctoral programmes. However, a recent study by Griffin et al (2022) described changing attitudes to the career decision among doctoral students, especially in STEM fields. The authors showed that doctoral students in STEM fields show less certainty about academic career choices compared to previous generations; instead, they express more interest in other career pathways, including non-research careers.…”
Section: Academic Career Development Of Engineering Phdsmentioning
confidence: 99%
See 3 more Smart Citations
“…This powerful interest in an academic career is related to the research training that they receive during doctoral programmes. However, a recent study by Griffin et al (2022) described changing attitudes to the career decision among doctoral students, especially in STEM fields. The authors showed that doctoral students in STEM fields show less certainty about academic career choices compared to previous generations; instead, they express more interest in other career pathways, including non-research careers.…”
Section: Academic Career Development Of Engineering Phdsmentioning
confidence: 99%
“…Structural aspects may include the economic environment, employment conditions in the labour market and relevant job market policies (Berglund & Wallinder, 2015;Tholen, 2015). However, as Griffin et al (2022) point out, individuals with higher levels of agency understand that individuals' abilities play more critical roles in successful career progress, despite structural constraints.…”
Section: Agency's Role In the Career Decisionmentioning
confidence: 99%
See 2 more Smart Citations
“…In the past few years, Studies in Graduate and Postdoctoral Education has published numerous articles which focus on this important area of research. One example is the article by Griffin et al (2023), which documented ways in which doctoral student agency shapes career decision-making. Based on interviews with students enrolled in a doctoral biology program, the authors emphasized how indecision is a common aspect of the career trajectory and can even be of benefit as students prepare for a range of options and potential transitions.…”
Section: Reflections On the Content Of The Journalmentioning
confidence: 99%